Improving care for older people with long-term conditions and social care needs in Salford: the CLASSIC mixed-methods study, including RCT - Peter Bower; David Reeves; Matt Sutton; Karina Lovell; Amy Blakemore; Mark Hann; Kelly Howells; Rachel Meacock; Luke Munford; Maria Panagioti; Beth Parkinson; Lisa Riste; et al. (National Institute for Health Research, 2018)
Background: The Salford Integrated Care Programme (SICP) was a large-scale transformation project to improve care for older people with long-term conditions and social care needs. We report an evaluation of the ability of the SICP to deliver an enhanced experience of care, improved quality of life, reduced costs of care and improved cost-effectiveness. Objectives: To explore the process of implementation of the SICP and the impact on patient outcomes and costs. Design: Qualitative methods (interviews and observations) to explore implementation, a cohort multiple randomised controlled trial to assess patient outcomes through quasi-experiments and a formal trial, and an analysis of routine data sets and appropriate comparators using non-randomised methodologies. Setting: Salford in the north-west of England. Participants: Older people aged ≥ 65 years, carers, and health and social care professionals. Interventions: A large-scale integrated care project with three core mechanisms of integration (community assets, multidisciplinary groups and an 'integrated contact centre'). Main outcome measures: Patient self-management, care experience and quality of life, and health-care utilisation and costs. Data sources: Professional and patient interviews, patient self-report measures, and routine quantitative data on service utilisation. Results: The SICP and subsequent developments have been sustained by strong partnerships between organisations. The SICP achieved 'functional integration' through the pooling of health and social care budgets, the development of the Alliance Agreement between four organisations and the development of the shared care record. 'Service-level' integration was slow and engagement with general practice was a challenge. We saw only minor changes in patient experience measures over the period of the evaluation (both improvements and reductions), with some increase in the use of community assets and care plans. Compared with other sites, the difference in the rates of admissions showed an increase in emergency admissions. Patient experience of health coaching was largely positive, although the effects of health coaching on activation and depression were not statistically significant. Economic analyses suggested that coaching was likely to be cost-effective, generating improvements in quality of life [mean incremental quality-adjusted life-year gain of 0.019, 95% confidence interval (CI) -0.006 to 0.043] at increased cost (mean incremental total cost increase of £150.58, 95% CI -£470.611 to £711.776). Limitations: The Comprehensive Longitudinal Assessment of Salford Integrated Care study represents a single site evaluation, with consequent limits on external validity. Patient response rates to the cohort survey were < 40%. Conclusions: The SICP has been implemented in a way that is consistent with the original vision. However, there has been more rapid success in establishing new integrated structures (such as a formal integrated care organisation), rather than in delivering mechanisms of integration at sufficient scale to have a large impact on patient outcomes. Future work: Further research could focus on each of the mechanisms of integration. The multidisciplinary groups may require improved targeting of patients or disease subgroups to demonstrate effectiveness. Development of a proven model of health coaching that can be implemented at scale is required, especially one that would provide cost savings for commissioners or providers. Similarly, further exploration is required to assess the longer-term benefits of community assets and whether or not health impacts translate to reductions in care use. Trial registration: Current Controlled Trials ISRCTN12286422. Funding: This project was funded by the NIHR Health Services and Delivery Research programme and will be published in full in Health Services and Delivery Research; Vol. 6, No. 31. See the NIHR Journals Library website for further project information.